1993
DOI: 10.3109/00498259309059444
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic studies of diosmin and diosmetin in perfused rat liver

Abstract: 1. The kinetics and metabolism of diosmin and diosmetin were investigated in the isolated perfused rat liver in order to assess the role of the liver. 2. Diosmetin and especially diosmin disappeared quickly from the perfusion medium. 3. Both flavonoids were rapidly metabolized and diosmetin was partly excreted in bile as the glucuronide and sulphate and diosmin was partly excreted in bile as such and as the glucuronide conjugate. 4. Diosmin and diosmetin did not appear to affect various parameters of liver fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Diosmin and diosmetin have been shown in other studies to be rapidly metabolized in perfused rat liver, and excreted in the bile as glucuronide and sulfate conjugates [135]. Boutin et al [136] found no free diosmetin in the blood or urine following 100 mg Kg -1 diosmin administration to rat.…”
Section: Metabolismmentioning
confidence: 97%
“…Diosmin and diosmetin have been shown in other studies to be rapidly metabolized in perfused rat liver, and excreted in the bile as glucuronide and sulfate conjugates [135]. Boutin et al [136] found no free diosmetin in the blood or urine following 100 mg Kg -1 diosmin administration to rat.…”
Section: Metabolismmentioning
confidence: 97%
“…In Europe, it is prescribed for treatment of venous insufficiency while in the US, it is marketed as a food supplement [60,61]. A study in rat liver perfusate showed that diosmin was mainly excreted in the bile as a glucuronide conjugate [62]. Glucuronides of diosmetin (diosmin aglycone) were detected on the apical side of Caco-2 cell culture [61].…”
Section: Diosminmentioning
confidence: 99%
“…Most flavonoid glycosides are deglycosylated by β-glucosidases in the small intestine; subsequently, the polyphenols are found in the blood as conjugates, glucuronate or sulfate, with or without methylation of the B-ring catechol functional group . According to several authors, the diosmin is metabolized by bacterial flora to form an aglycone, diosmetin, which is then metabolized to form glucuronides and sulfate, the major metabolite , . As in the case of diosmin, the first metabolite formed with rutin is the aglycone quercetin.…”
Section: Anticarcinogenic Propertiesmentioning
confidence: 99%